2004
DOI: 10.1016/j.brainres.2003.10.076
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differences between planes of section do not influence the electrophysiological properties of identified rat dorsal motor nucleus of the vagus neurons

Abstract: Recent cytoarchitectonic studies have shown that the dorsal motor nucleus of the vagus (DMV) comprises neurons with different morphological features. Our own studies, conducted in horizontal brainstem slices, have shown that DMV neurons projecting to stomach areas can be distinguished from neurons projecting to the intestine on the basis of their electrophysiological as well as morphological properties. The majority of the in vitro experimental investigations, however, have been conducted on coronal brainstem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…In the mouse, these include a small number of GABAergic neurons. Overall, the properties of neurons retrogradely labeled subsequent to inoculation of the stomach with PRV-152 or PRV-614 were similar to those reported previously for gastric-projecting DMV cells (Browning et al, 1999; Valenzuela et al, 2004), validating this labeling technique in these cells. Whereas retrogradely transported labels such as FluoroGold are as likely to be taken up by injured axons or axons of passage as by terminals, PRV preferentially infects terminal fields over axons of passage (Card et al, 1993; Ch’ng et al, 2007), resulting in a larger pool of cells selectively labeled gastric-related neurons.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the mouse, these include a small number of GABAergic neurons. Overall, the properties of neurons retrogradely labeled subsequent to inoculation of the stomach with PRV-152 or PRV-614 were similar to those reported previously for gastric-projecting DMV cells (Browning et al, 1999; Valenzuela et al, 2004), validating this labeling technique in these cells. Whereas retrogradely transported labels such as FluoroGold are as likely to be taken up by injured axons or axons of passage as by terminals, PRV preferentially infects terminal fields over axons of passage (Card et al, 1993; Ch’ng et al, 2007), resulting in a larger pool of cells selectively labeled gastric-related neurons.…”
Section: Discussionsupporting
confidence: 85%
“…Putative interneurons with smaller somata have also been reported in the nucleus (McLean and Hopkins, 1981; 1982; Blessing et al, 1984; Blessing, 1990; Izzo et al, 1992; Fox and Powley, 1992; Huang et al, 1993; Streefland et al, 1998; Jarvinen and Powley, 1999), but axon trajectories of these cells have not been well-characterized. Several studies have indicated that DMV motor neurons have a small but detectable degree of heterogeneity with regard to functional, morphological, electrophysiological attributes (Huang et al, 1993; Fogel et al, 1996; Browning et al, 1999; Valenzuela, et al, 2004). The morphological details of putative interneurons have never been reported (Jarvinen and Powley, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Huang et al, have suggested that within the human brainstem, DMV neurons display distinctive morphological properties and are organized into functionally specific groups that innervate particular visceral organs (239). In support of this, studies in rodents have demonstrated that DMV neurons are morphologically heterogeneous (74, 169, 252, 317) and our studies have shown that the biophysical and morphological properties of DMV neurons are correlated with their target organ within the GI tract (74). In brief, it appears that DMV neurons projecting to the gastric fundus are smaller and have fewer dendritic branches as compared to other GI-projecting DMV neurons, with neurons projecting to the large intestine having the largest soma size (74,317).…”
Section: Properties and Organization Of Vagal Efferent Motoneuronssupporting
confidence: 80%
“…In support of this, studies in rodents have demonstrated that DMV neurons are morphologically heterogeneous (74, 169, 252, 317) and our studies have shown that the biophysical and morphological properties of DMV neurons are correlated with their target organ within the GI tract (74). In brief, it appears that DMV neurons projecting to the gastric fundus are smaller and have fewer dendritic branches as compared to other GI-projecting DMV neurons, with neurons projecting to the large intestine having the largest soma size (74,317). In addition, functional studies have also demonstrated that DMV neurons sensitive to gastric distention are morphologically different from those that respond to intestinal distention (164).…”
Section: Properties and Organization Of Vagal Efferent Motoneuronssupporting
confidence: 80%
“…Soma Surface, Number of Branch. As natural morphology is closely related to neuronal characteristics and functions [1], [2], [3], [4], neuroscientists make great efforts to study on neurons from the perspective of neuronal morphology, and have achieved fruitful achievements [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%